Infeertilidad y duelo perinatal - Teresa Mª Martínez-Mollá; Mª Esperanza Martínez-Ruiz (Musas, 2024)
INTRODUCTION: The age increases in the will to conceive haveled to an increase in the difficulty of reproduction that is being compensated by the development of assisted reproduction techniques; however, the feelings accompanying their use are the same as in perinatal grief while not always recognized. OBJECTIVE.To explore the feelings of grief of women and their partners in the sterility process, from the moment they access the first sterility consultation at the Hospitals of San Juan and Alcoy until the referral to in vitrofertilization techniques. METHODOLOGY.Qualitative research from the phenomenological perspective. Data collection through individual in-depth interviews. The information was recorded, transcribed, coded, triangulated, and interpreted. Analysis using the validated Atlas-ti 8 tool. RESULTS.Three categories were identified: psychological, social and spiritual feelings. Those are, in turn, grouped into twelve subcategories: anxiety, frustration, sadness, fear, emotional ambivalence, justification, loneliness, trivialization, search for meaning, guilt and acceptance. CONCLUSION.Couples included in assisted reproduction programsexpressed feelings of grief that match perinatal grief (anxiety, fear, frustration, ambivalence, social isolation, trivialization, search for meaning, guilt and acceptance). Gender differences continue to exist. The support of family, friends, and professionals is essential. The need to improve the quality of care is evident: with a continuity of professionals, with theirtrainingto provide comprehensive care and with the existence of protocols